The process of the prisoners's social rehabilitation as inharmonious development of identity - Barbara Toroń-Fórmanek (Maria Curie-Skłodowska University, Lublin, Poland, 2017)
Resocialization activities aim up to lead a person to adequate state of adaptation to lifestyle standards, to develop features, that empower socialisation and coexistence in culture, and what follows, also to develop man's identity. The theory, unfortunately does not come along with practice, what author's research proves. The article presents assumptions of penitentiary socialisation according to definition of human identity. Process of it's development is beeing linked by the author with both Walter's lifestyle conception and her own research which both shows that resocialisation by Polish prison system doesn't affect the process of redevelopment of imprisoned man's indentity positively. Author finds the reason in equally imprisonment, deprivation of individual needs and growing into deviant subculture. She notices a connection in developing of criminal identity with influence of school enviroment, peer and crime-related groups. Simultaneously she finds the way to improve the shown above situation by methods of constructive resocialisation, which allows individual identity to develop in a peaceful and balanced way.